(untitled) (Research, Society and Development, 2020)
This article was developed in the subject of Tópicos em Ensino de Letras, ministered during the first semester of 2019, in the master’s course in Humanities and Languages, of Universidade Franciscana, UFN, Santa Maria, RS. This subject aims to discuss, from the perspective of humanities and languages teaching, the relation between literacy, multiliteracies and discourse genres, in order to produce learning products for basic education in the filed of Letters. In order to make classes more dynamic, the students were proposed pedagogical practices that explore the use of active methodologies. So, as part of the activities, each pair of students used a learning strategy (CAMARGO; DAROS, 2018), for the debates about the texts. As a product of this expeirence, each student produced a cientific article representing the learning process throughout the subject. This way, the theoretical investigation aims to ponder on the contribution of active methodologies for more dyamic pedagogical praxis so to surpass the exclusively traditional and technical teaching. For this purpose, a bibliographic research was held, with books abd cientific articles for the understanding and deepening of informations about the discussed subject. The work results enabled the students to analyze the potentialities of active methodologies for the comprehension of how it is possible to work literacy, multiliteracies and discourse genres interrelatedly and actively at the basic school. In conclusion, the use of active methodologies involves the scholar actively, enabling his/her learning, for they try out inumerous new possibilities.